Certificação participativa e compra coletiva de alimentos ecológicos: redes locais construindo mercados cooperativos, um estudo na região de Campinas - São Paulo - Tassi, Maria Elisa Von Zuben (2011)
The countryside 'modernization' and the cities development in recent years have shown a growing rift in the relationship between man and nature, and consequently the decrease in family and ecological agricultural practices. This research investigates the extent to which markets, herein defined as a set of multiple actors and relationships, can be one of the links between urban and rural life, mediating exchanges between consumers and ecological farmers. An attempt was also made to systematize the experiences of certification and marketing of basic ecological foodstuffs and sociotechnical arrangements that have been pursued in the metropolitan area of Campinas. This region is known today as a scientific-technological and tourism polo which has been expanding its urban boundaries upon consolidated fruit and vegetable family farms. The theoretical approach was based on multiple contributions as Agroecology, the New Economic Sociology, the Fair Trade, and conceptual inputs regarding strategies for Rural Development. It was adopted an action-research methodology with distinct and inter-related groups: the Participative Guarantee System (PGS), coordinated by the Association of Natural Agriculture of Campinas and region (ANC) and the collective organic products buying group - Green Exchange, besides the reconstruction of historical path of social representations. The regulation of organic agriculture (Federal Law 10.830/2003) including PGSs as mechanisms for quality control; Solidarity Economy (National System of Fair Trade - 2010) as well as incentive programs to family farming and Agroecology are factors that have favored the consolidation of socio-technical networks and marketing with cooperative principles, enhanced construction, validation and exchange of skills and knowledge among farmers, technicians and consumers. However, the challenges to the growth of organic production range from revaluation of family farming to the inherent losses in the production cycles and trade, including the shortage of workers in the field, low technical and administrative assistance to farmers and logistics integration for product 14 distribution. The alternatives found involve collective territorialized projects and networking, seeking a closer relationship between consumer and producer through structures and agreements of mutual support, as the experiences of Community Supported Agriculture (CSA). Thus, the adoption of political and community strategies are fundamental to maintaining and strengthening family farms ecologically based and local markets, as well as rural development on a sustainable basis.